Alteration of nociceptive integration in the spinal cord of a rat model of Parkinson's disease. Issue 6 (18th May 2018) - Charles, Keri‐Ann; Naudet, Frédéric; Bouali‐Benazzouz, Rabia; Landry, Marc; De Deurwaerdère, Philippe; Fossat, Pascal; Benazzouz, Abdelhamid
ABSTRACT: Background : Pain is a major non motor symptom that contributes to impaired quality of life in PD. However, its mechanism is unknown. Objectives and Methods : We sought to identify the pain phenotypes and parallel changes in spinal integration of peripheral stimuli in a rat model of PD induced by lesions of SN dopamine neurons, using behavioral plantar and von Frey tests as well as electrophysiology of the dorsal horn. Results : We show that dopamine depletion by 6‐OHDA induced hypersensitivity to mechanical and thermal stimuli. These abnormal behaviors were paralleled by increased neuronal responses and hyperexcitability of wide dynamic range neurons of lamina V of the dorsal horn of the spinal cord in response to electrical stimulation of the sciatic nerve in the 6‐OHDA model as compared to sham rats. Conclusions : These results provide evidence for alteration of nociceptive integration in the spinal dorsal horn neurons in 6‐OHDA rats that can reflect changes in pain behavior. © 2018 International Parkinson and Movement Disorder Society